PENDAMPINGAN MAHASISWA PADA KEGIATAN BERBAKTI, MENGABDI, BERBAGI DI DESA PENAMPANGAN - Br Sembiring, Ribka Kariani; Sipayung, Regina; Sitorus, Tania; Abigail, Martina (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
This community service was carried out in Penampangan Village, Samosir Regency in the context of implementing Community Service Lectures (KKN) in KKN subjects accompanied by field supervisors. This community service activity is carried out as a student learning process through dedication, service and sharing in activities directly in the community. The purpose of this activity is to develop student competency in applying the knowledge, skills and attitudes they already have, so they are able to design and implement social contribution programs in society based on their field of knowledge; Together with the community, collaborate in improving the skills, education, and standard of living of local residents; Provide education and practice of technology-based learning innovations to school children at the elementary, junior high, high school and equivalent levels while students are active in Penampangan Village. The result of this activity is that the implementation of the teaching KKN work program has been carried out successfully. The community was very enthusiastic and provided self-help assistance both material and in-material for the work programs carried out by KKN participants. Even though there are a few obstacles, all of them can be overcome with enthusiasm and good cooperation by KKN members and the support of the village community. The peak activity of the KKN implementation is the release and distribution of mementos to village officials, children of learning houses, and community leaders of Panampangan Village.